(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The Internet of Things (IoT) is a new technology that uses billions of embedded sensors from many suppliers to continually detect data based on context and transmit that data to a central database through the internet. The necessary context is provided by data analytics. This leads to a pleasant existence with little to no human interference. Understanding the basic components necessary to develop IoT and also the combination of various communication technologies is the most significant aspect of IoT. This study presents a comprehensive overview of the most recent advancements in this exciting new field, including the most cutting-edge methodologies, protocols, and applications. This study suggests a new classification scheme for Internet of Things (IoT) technologies and provides examples of some of the most significant IoT technologies, and characteristics of some applications that could significantly improve the quality of life, particularly for the elderly and people with disabilities. This study is also far broader in scope, including a variety of different technologies, from sensors to software.